The Development of Professional Empowerment Program for Principals by Interorganizational Collaboration and Action Research - Peiying Chen; Tzu-Bin Lin (National Taipei University of Education, 2015)
As an action research approach through interorganizational collaboration, this study aims to develop an effective professional learning program for enhancing principals' leadership. There are three phases in this research: program design, implementation, and feedback and reflection. With a comprehensive literature review and focus group interviews, key competences of leadership were identified. The program contents were designed through interorganizational collaboration between academics, local officers, experienced principals, and NGO practitioners. The program contains self-awareness and team building in the dark, leading for the future, curriculum and instructional leadership, systems thinking, Understanding by Design, framework and practice, and World Café dialogue. In Phase II, a four-day workshop program has been held twice in the summer of 2012. Learning feedback was posted on Facebook as informal formative evaluation during the implementation phase. In phase III, opinions and feedbacks from learners, external observers, and curriculum designers were collected to assess the effectiveness of the program. The challenges and revision ideas were proposed at the end of the paper. Through the cycle of "design-act-feedback-revision" of action research with interorganizational collaboration, the present professional development program for principals can be refined and better empower school leaders with new ways of situated learning, collaboration, and reflective thinking. Although this program has been implemented for a few times in the past two years, this paper only explained and discussed the merits and effects of the workshops implemented in the summer of 2012.